Eksistensi Badan Usaha Milik Desa (BUMDes) Dalam Perspektif Ajaran Bung Karno Untuk Meningkatkan Kesejahteraan Rakyat - Ismail, Ismail; Fakhris Lutfianto Hapsoro (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2023)
One of Indonesia's founding fathers, Bung Karno, taught the principle of people's welfare which is enshrined in the Fifth Precept, namely Social Justice for All Indonesian People. The issuance of Law No. 6/2014 on Villages philosophically applies the value of the 5th Precept of Pancasila, a very significant substance is to change the paradigm of village development which previously only placed the village as an object of development, now turning into the main subject of development. One of the efforts to realize the values of Bung Karno's teachings, especially the value of people's welfare, is through the establishment of Village-Owned Enterprises (BUMDes). However, in its implementation, there are several problems such as the lack of understanding of village officials, especially the Village Head regarding BUMDes, inadequate mastery of managerial skills and rampant corruption in the Village.